1983
DOI: 10.2118/10597-pa
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into Strontium and Calcium Sulfate Scaling Mechanisms in a Wet Producer

Abstract: On-going field scaling tests have provided a unique opportunity to study how strontium sulfate and calcium sulfate scales are formed in an oil-producing well. Results indicate that development of nucleation sites on tubing surfaces is the most critical step. Scale profiles within a wellbore are determined mainly by kinetics of crystallization, well-fluid dynamics, and tubing surface characteristics and, especially, synergistic effects of these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The advantage of using experimental solubility data is that the activities of the respective metal ions and the anion of interest need not be determined directly but are included implicitly in the conditional constants. Solubility data were obtained from the literature for gypsum (Blout and Dickson, 1973; Liu and Nancollas, 1971; Nancollas et al, 1978; Shen and Corsby, 1983; , for hemihydrate and anhydrite (Tempelton and Rodgers, 1960), for celestite (Liu and Nancollas, 1971), and barite (Collins and Leinweber, 1956; Leon and Scott, 1987; Lindlof and Stoffer, 1983). Pressure data for the CaSO, systems can be found in or calculated from data given in Collins and Leinweber (1 956), Davis and Collins (1971), Hunton and Gilbert (1982), Nancollas and Liu (1975) and Tempelton (1960).…”
Section: Estimation Of Scale Formation Potentialmentioning
confidence: 99%
“…The advantage of using experimental solubility data is that the activities of the respective metal ions and the anion of interest need not be determined directly but are included implicitly in the conditional constants. Solubility data were obtained from the literature for gypsum (Blout and Dickson, 1973; Liu and Nancollas, 1971; Nancollas et al, 1978; Shen and Corsby, 1983; , for hemihydrate and anhydrite (Tempelton and Rodgers, 1960), for celestite (Liu and Nancollas, 1971), and barite (Collins and Leinweber, 1956; Leon and Scott, 1987; Lindlof and Stoffer, 1983). Pressure data for the CaSO, systems can be found in or calculated from data given in Collins and Leinweber (1 956), Davis and Collins (1971), Hunton and Gilbert (1982), Nancollas and Liu (1975) and Tempelton (1960).…”
Section: Estimation Of Scale Formation Potentialmentioning
confidence: 99%
“…The solubility product constants (K sp ) for different carbonate and sulfate scales decrease with temperature for a temperature range of 60-300°F (Nassivera and Essel 1979;Essel and Carlberg 1982;Shen and Corsby 1983). Oddo et al (1991); Oddo and Tomson (1994) showed that the formation of calcium sulfate scale depends on temperature and does not depend on pH and can precipitate at low as well as high pH values.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the field scale barium sulfate deposits also contain strontium sulfate (Essel and Carlberg, 1982;Shen and Corsby, 1983).…”
Section: Strontium Sulfate Scalementioning
confidence: 99%